Genetic variability in 12 butterfly pea (Clitoria ternatea L.) accessions: a dual approach with cluster and principal component analysis - Algina, Azka; Ustari, Debby; Wicaksono, Arif Affan; Concibido, Vergel; Karuniawan, Agung (Jurusan Agroteknologi, 2024)
Understanding genetic variability is crucial for enhancing the breeding programs of butterfly pea (Clitoria ternatea L.), particularly in the face of the demand for improved crop varieties. This study aims to (i) evaluate the genetic variability of 12 butterfly pea accessions based on 28 agro-morphological traits and (ii) analyze the genetic relationships among these accessions. The research was conducted from December 2022 to October 2023 at the Ciparanje Experimental Field, Faculty of Agriculture, Universitas Padjadjaran. The experimental design employed a Randomized Complete Block Design (RCBD) with 12 accessions and three replications. Observations were made on 28 agro-morphological traits. Data analysis was performed using analysis of variance (ANOVA), principal component analysis (PCA), and agglomerative hierarchical clustering (AHC). ANOVA results indicated significant diversity among the 12 accessions based on 17 agro-morphological traits. PCA results showed that the first six principal components accounted for 89.1% of the total genetic variability and identified all traits as contributing factors to the genetic variability among the accessions. AHC analysis grouped the accessions into two main clusters, with Euclidean distances ranging from 1.00 to 4.00, indicating varying levels of genetic relatedness. These findings underscore the importance of genetic variability in formulating breeding strategies, particularly in the selection of parents based on targeted agro-morphological traits. ABSTRAK Informasi keragaman genetik sangat penting untuk mendukung program pemuliaan tanaman telang (Clitoria ternatea L.), khususnya dalam menghadapi permintaan varietas unggul. Penelitian ini bertujuan untuk (i) mengevaluasi keragaman genetik dari 12 aksesi kembang telang berdasarkan 28 karakter agro-morfologi dan (ii) menganalisis hubungan genetik di antara aksesi-aksesi tersebut berdasarkan 28 karakter agro-morfologi. Penelitian dilaksanakan pada Desember 2022 hingga Oktober 2023 di Kebun Percobaan Ciparanje, Fakultas Pertanian, Universitas Padjadjaran. Desain eksperimen menggunakan Rancangan Acak Kelompok Lengkap (RAKL) dengan 12 aksesi dan tiga ulangan. Pengamatan dilakukan pada 28 karakter agro-morfologi. Analisis data dilakukan dengan analisis varians (ANOVA), analisis komponen utama (PCA), dan pengelompokan hierarki aglomeratif (AHC). Hasil analisis ANOVA menunjukkan bahwa 12 aksesi telang beragam secara signifikan berdasarkan 17 karakter agro-morfologi. Hasil PCA menunjukkan bahwa enam komponen utama pertama menjelaskan 89,1% dari total keragaman genetik dan mengidentifikasi 28 karakter agro-morfologi sebagai karakter yang berkontribusi terhadap keragaman genetik 12 aksesi telang. Analisis AHC mengelompokkan 12 aksesi menjadi dua kelompok utama dengan jarak Euclidean berkisar antara 1,00 hingga 4,00, mengindikasikan tingkat kekerabatan genetik yang jauh. Temuan ini menegaskan pentingnya keragaman genetik dalam merumuskan strategi pemuliaan yang efektif, terutama dalam pemilihan tetua berdasarkan karakter agro-morfologi yang ditargetkan.